Globe stability during simulated vitrectomy with valved and non-valved trocar cannulas - Abulon DJ (Dove Medical Press, 2015)
Dina Joy Abulon,1 Martin Charles,2 Daniel E Charles21Global Medical Affairs, Alcon Laboratories, Inc., Lake Forest, CA, USA; 2Centro Oftalmológico Dr Charles, Buenos Aires, ArgentinaPurpose: To compare the effects of valved and non-valved cannulas on intraocular pressure (IOP), fluid leakage, and vitreous incarceration during simulated vitrectomy.Methods: Three-port pars plana incisions were generated in six rubber eyes using 23-, 25-, and 27-gauge valved and non-valved trocar cannulas. The models were filled with air and IOP was measured. Similar procedures were followed for 36 acrylic eyes filled with saline solution. Vitreous incarceration was analyzed in eleven rabbit and twelve porcine cadaver eyes.Results: In the air-filled model, IOP loss was 89%–94% when two non-valved cannulas were unoccupied versus 1%–5% when two valved cannulas were unoccupied. In the fluid-filled model, with non-valved cannulas, IOP dropped while fluid leaked from the open ports. With two open ports, the IOP dropped to 20%–30% of set infusion pressure, regardless of infusion pressure and IOP compensation. The IOP was maintained in valved cannulas when one or two ports were left open, regardless of IOP compensation settings. There was no or minimal fluid leakage through open ports at any infusion pressure. Direct microscopic analysis of rabbit eyes showed that vitreous incarceration was significantly greater with 23-gauge non-valved than valved cannulas (P<0.005), and endoscopy of porcine eyes showed that vitreous incarceration was significantly greater with 23-gauge (P<0.05) and 27-gauge (P<0.05) non-valved cannulas. External observation of rabbit eyes showed vitreous prolapse through non-valved, but not valved, cannulas.Conclusion: Valved cannulas surpassed non-valved cannulas in maintaining IOP, preventing fluid leakage, and reducing vitreous incarceration during simulated vitrectomy.Keywords: IOP, fluid leakage, vitreous incarceration